DIABETES MELLITUS IN COMBINATION WITH CORONARY HEART DISEASE - Normatov Murodjon Buribayevich; Yarmatov Suvon Tatlibayevich (Scholar Express Journals, 2023)
The article is devoted to the study of the prognosis and course of Diabetes mellitus in combination with coronary heart disease. Also in this article, the features of biochemical blood parameters in patients in the study group are highlighted. An important problem at the moment is carbohydrate metabolism disorders, which in turn worsen the prognosis of patients with CVD. The prevalence of diabetes mellitus (DM) in patients with coronary heart disease (CHD) reaches 20-30%, 70% have newly diagnosed DM or impaired glucose tolerance (HTG).
Keywords: Diabetes mellitus; coronary heart disease; homocysteine; glucose